PENERAPAN E-LKPD BERBASIS SAINTIFIK INKUIRI TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS 5 - Anna Qurrotul Ain; Syachruroji, Ahmad; Rakhman, Patra Aghtiar (Program Studi Tadris Matematika dan Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Universitas Islam Negeri (UIN) Datokarama Palu, 2024)
This study aims to determine the application of E-LKPD based on scientific inquiry on critical thinking skills in grade V science subjects at SDN Karawaci 1. The research method used is quasi-experiment with a research design of nonequivalent control group design. There are two classes in this study, namely the experimental class and the control class. The experimental class consisted of 25 students who applied learning using E-LKPD based on scientific inquiry and the control class consisted of 25 students who applied conventional LKPD. The research data collection used observation instruments, pretests and posttests. Data analysis was carried out using descriptive statistics and inferential statistics. Inferential statistical data analysis using independent sample t-test one party right and n-gain. Based on the data analysis calculations that have been carried out by researchers, the research results obtained are the critical thinking skills of students who use E-LKPD are better than the critical thinking skills of students who use LKPD. Through the research that has been done, it is hoped that this research will be a motivation and innovation in learning and provide information to readers, teachers and other educators about the importance of developing critical thinking skills for elementary school students